Pengaruh Pengembangan Karyawan Danmotivasi Kerja Terhadap Kinerja Karyawan (GEMA EKONOMI, 2023)
Changes in organizational environment increasingly complex and competitive so that human resources are the main asset of any organization as employees determine the success of the organization in achieving organizational goals. The development of quality human resources to support the success of management in the development of employee motivation is also needed in order to achieve labor productivity and job satisfaction of subordinates. Employee performance is the result of work accomplished person or group of people, in order to obtain the right employees - truly qualified according to the needs of the organization, and therefore researchers interested in doing research in PO. Puspa Jaya, Bandar Lampung.Problems faced by PO. Puspa Jaya is a transition position of the conductor becomes very slow drivers and outcomes should have been more than achieved. This is an indication of employee development at PO. Puspa Jaya Bandar Lampung less going well, so formulated problems "Is employee development and motivation affect the performance of employees at the PO. Puspa Jaya Bandar Lampung ".The hypothesis is employee development has positive influence on employee performance, motivation positive effect on employee performance and employee development and motivation to work together positive influence on employee performance. The calculation is based on the results of significant value employee development amounted to 0.002 <0.05 and motivational significance value of 0.000 <0.05. Also be obtained from the calculation of the probability of employee development and motivation on the performance of the PO. Puspa Jaya Bandar Lampung are 0.302 and 0.413.The conclusions in this study is the lack of employees in career advancement opportunities and the lack of coordination in the work. Suggestions researcher for the leadership of the PO. Puspa Jaya Bandar Lampung have to pay attention to in the development of human resources, providing opportunities to gain higher office, and improve coordination so that the performance of employees will increase